A review focuses on a neglected and controversial component of SCI: myelin debris - Zhou, Yuchen; Xu, Tao; Zhou, Yiyan; Han, Wei; Wu, Zhengchao; Yang, Changwei; Chen, Xiaoqing (Frontiers in Immunology, 2024)
Myelin sheath, as the multilayer dense structure enclosing axons in humans and other higher organisms, may rupture due to various injury factors after spinal cord injury, thus producing myelin debris. The myelin debris contains a variety of myelin-associated inhibitors (MAIs) and lipid, all inhibiting the repair after spinal cord injury. Through summary and analysis, the present authors found that the inhibition of myelin debris can be mainly divided into two categories: firstly, the direct inhibition mediated by MAIs; secondly, the indirect inhibition mediated by lipid such as cholesterol. It is worth noting that phagocytes are required in the latter indirect inhibition, such as professional phagocytes (macrophages et al.) and non-professional phagocytes (astrocytes et al.). Moreover, complement and the immune system also participate in the phagocytosis of myelin debris, working together with phagocytes to aggravate spinal cord injury. In conclusion, this paper focuses on the direct and indirect effects of myelin debris on spinal cord injury, aiming to provide new inspiration and reflection for the basic research of spinal cord injury and the conception of related treatment.